Non-competitive NMDA antagonist MK-801 prevents memory reconsolidation impairment caused by protein synthesis inhibitors in young chicks - Tiunova, A. A.; Bezriadnov, D. V.; Anokhin, K. V. (Frontiers in Pharmacology, 2024)
Introduction: Reactivation of already consolidated memory can initiate its destabilization, making the memory trace labile. Normally, this destabilization is followed by reconsolidation of the memory trace, enriched by newly acquired experience. Disrupting the reconsolidation process, for example, by inhibiting protein synthesis, impairs subsequent memory retrieval, leading to reminder-related amnesia. Previous studies in various species have shown that this impairment can be prevented by using NMDA receptor antagonists, which interfere with memory destabilization. Methods: In the present study we examined this phenomenon using a one-trial passive avoidance learning model in newborn chicks, the hypothesis being that inactivation of the NMDA-mediated transmission during memory reactivation would inhibit the memory trace labilization and thus prevent the reminder-related amnesia. Results: We found that reminder-associated administration of the NMDA receptor antagonist MK-801 or one of the protein synthesis inhibitors (anisomycin, cycloheximide, 2-deoxygalactose) each alone produced amnesia. However, when combined, injection of MK-801 before the reminder prevented amnesia induced by protein synthesis inhibitors. Discussion: We suggest that the observed paradoxical effect implicates the involvement of NMDA receptors in both protein synthesis-independent engram destabilization upon its retrieval and protein synthesismediated engram stabilization after its updating. This puzzling dual role of NMDA receptors in memory destabilization/restabilization requires further investigation.